Irish civil society: rearranging the deckchairs on the Titanic? A case study of fighting Irish social security retrenchment. Issue 1 (2nd January 2016) - Murphy, Mary P.
ABSTRACT: Examining the politics of Irish responses to crisis-related social security cuts gives insight into Irish agency and how crisis has shaped the contours of Irish civil society. Despite assertions of lack of protest, Irish retrenchment was resisted and sometimes partially defeated. Using political sociology frameworks to explore interactions between institutional, ideological and interest variables in three case studies of defending cuts enables analysis of resistance strategies. There are tensions when short-term defensive resistance strategies undermine or limit offensive political coalition-building that might offer greater long-term solidarity and more sustainable resistance to intensification of the neoliberal Irish welfare state.